Investigating drivers of hidden student support cost in an open distance learning environment of South Africa - Le Roux, L; Kembo, J; Tustin, DH (South African Journal of Higher Education, 2016)
In the open distance learning (ODL) sphere there are invariably incremental student support costs that largely remain unaccounted for and might not be readily apparent. From an educational perspective this raises serious concerns given that effective on and off-line student support could potentially reduce the intrinsic cost of studying at ODL institutions. Typical hidden student support service costs in ODL are rooted in areas such as information technology, registration, contact centre, lecturing and tutoring and human resources/administration support. The relevance of these hidden costs becomes pertinent when comparing the contribution of student support from a geographic perspective. Students from remote areas seemingly seek higher levels of support and assumingly cause higher hidden student support costs to educational institutions. Against this background, this article does not intend to provide actual costing, but rather provides an early exposition of relevant cost drivers that impact on student retention, throughput and success in ODL.